Role of maternal serum ferritin as a predictive marker in intrauterine growth restriction - Bindal, Neeta; Godha, Zeepee; Kohli, Reema; Kadam, V. K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Intrauterine growth restriction (IUGR) is most common and distressing complication for both obstetrician and neonatologist. Measurement of maternal serum ferritin has also been used as a predictive marker of increase risk of IUGR. In pregnancy, ferritin level decreases with advancing gestation. Its lowest level is seen around 30-32 weeks of gestational age after which its concentration reaches plateau level. Methods: Total 326 antenatal women enrolled in the study. Maternal serum samples of all women were taken at 25th week and again at 30-32 weeks in trace free mineral evacuated tubes for assessment of serum ferritin by chemiluminescence. Mean of both values was calculated. Results: Mean ferritin value of women with average for gestational age neonates was 15.49 ng/ml and women with growth restricted neonates was 19.71 ng/ml. The women with mean serum ferritin above 20 ng/ml, were 6.26 times more likely to have asymmetrically growth restricted baby and 4.47 times more likely to have a symmetrically growth restricted baby when compared to women with serum ferritin value less then <20 ng/ml. Conclusions: In our study negative correlation was found between the value of serum ferritin and neonatal birth weight. In future large randomized control trial is needed to found association between maternal serum ferritin and IUGR.